The Impact of the PBL Models Helping iSpring Presenters on Student HOTS Literacy on Reaction Rate - Surya Panangian Munthe; Retno Dwi Suyanti (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2023)
Science literacy in social life is a very important competence for students as it relates to their ability to link problems in science with their perspective as citizens. One of the logical consequences of the need for teacher professionalism in the presentation of chemistry learning is the teacher's ability to create the right learning strategies that fit the problems facing today's education world. The transfer of old learning methods to new ones is one way to solve the problem. The aim of this study is to find out whether the increase in HOTS literacy occurs when the PBL model is integrated with the iSpring Presenter media on the Reaction Speed material in class XI SMA. The research will also explain the most evolving HOTS element of literacy. This study is a Quantitative Descriptive Study using experimental methods with One-Group Pretest-Posttest Design. The results of the study showed that the literacy ability of HOTS students improved through learning with the PBL model with iSPring Presenter media, this was demonstrated through the t test obtained thitung values > tables (10,55 > 2,032245) with N-gain values of 0.7639 (76.39%).